2011
DOI: 10.1097/hjh.0b013e32834bbb6b
|View full text |Cite
|
Sign up to set email alerts
|

Renin–angiotensin and sympathetic nervous system contribution to high blood pressure in Schlager mice

Abstract: The hypotensive actions of losartan suggest that although the RAS provides an important contribution to BP, it contributes little, if at all, to the hypertension-induced or the greater stress-induced pressor responses in Schlager mice. The effects of pentolinium suggest that the SNS is mainly responsible for hypertension in BPH/2J mice. However, the RAS inhibits sympathetic vasomotor tone during inactivity and prolongs sympathetic activation during periods of adverse stress, indicating an important sympatho-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 46 publications
2
19
0
Order By: Relevance
“…BPH/2J mice are a model of lifelong hypertension on a genetic basis and manifest some of the cardinal features of essential hypertension, i.e., neurohumoral dysfunction, sympathetic activation, cardiac hypertrophy, and kidney atrophy (58,59). Due to long-lasting hypertension, BPH/2J mice are valuable in hypertension research, akin to spontaneously hypertensive rats.…”
Section: Discussionmentioning
confidence: 99%
“…BPH/2J mice are a model of lifelong hypertension on a genetic basis and manifest some of the cardinal features of essential hypertension, i.e., neurohumoral dysfunction, sympathetic activation, cardiac hypertrophy, and kidney atrophy (58,59). Due to long-lasting hypertension, BPH/2J mice are valuable in hypertension research, akin to spontaneously hypertensive rats.…”
Section: Discussionmentioning
confidence: 99%
“…Restraint stress involved guiding the mouse into a cylindrical Plexi glass restrainer with a sliding back plate to confine the mouse without applying physical pressure. More detail is provided in previous publications [1,2,4,5,[22][23][24].…”
Section: Assessment Of Cardiovascular Reactivity In Response To Stresmentioning
confidence: 99%
“…This is based on the ability of the ganglion blocker pentolinium to abolish the blood pressure (BP) difference between normotensive BPN/3J and BPH/2J mice while blockade of the renin-angiotensin system had an equal hypotensive effect in both strains [2]. Thus, it is likely that there is a greater sympathetic contribution to the hypertension in BPH/2J mice.…”
Section: Introductionmentioning
confidence: 99%
“…This KD mouse displays a decrease in the release of ACh of 40% and 70%, respectively, for heterozygous and homozygous (HOM) individuals (55, 56). Due to its parasympathetic impairment, the VAChT KD HOM mouse model (31) may be quite useful for studying pathophysiological processes involving sympathovagal imbalance (22,23,50,62).It has also been demonstrated that individuals with several disorders affecting the autonomic nervous system and cardiac function, e.g., heart failure, myocardial infarction, diabetes, and hypertension, have loss of daily variations in cardiovascular parameters (1,7,21,37,54,74,77). Moreover, a decrease in heart rate (HR) variability (27) and baroreflex sensitivity (BRS) (51) as well as an exaggerated cardiovascular response to stress have been described under these pathological conditions (10,11,49) and associated with higher cardiovascular risk (13,78).…”
mentioning
confidence: 99%
“…This KD mouse displays a decrease in the release of ACh of 40% and 70%, respectively, for heterozygous and homozygous (HOM) individuals (55, 56). Due to its parasympathetic impairment, the VAChT KD HOM mouse model (31) may be quite useful for studying pathophysiological processes involving sympathovagal imbalance (22,23,50,62).…”
mentioning
confidence: 99%